2011
DOI: 10.1002/qj.970
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting of precipitation by an NWP model using assimilation of extrapolated radar reflectivity

Abstract: Two methods for assimilating radar reflectivity into the COSMO numerical weather prediction (NWP) model were compared to precipitation forecasts. The first method assimilated observed radar reflectivity, and the second one assimilated observed and extrapolated radar reflectivity. The assimilation technique was based on the correction of the model's water vapour mixing ratio. The extrapolation was performed by the COTREC method and was 1 hour long. The model's horizontal resolution was 2.8 km.The comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Extrapolation methods, discussed above, calculate the prediction for a given place and a given time by transferring the existing precipitation field along Lagrangian trajectories. Frequently, these methods assume that precipitation does not change over the time along the trajectories e.g., [91,[98][99][100][101][102][103][104]. This assumption is acceptable in case of stratiform precipitation for forecasts with lead times of several hours; however, in case of convective precipitation, the precipitation can change (even significantly) along the trajectories.…”
Section: Quantitative Precipitation Forecastmentioning
confidence: 99%
“…Extrapolation methods, discussed above, calculate the prediction for a given place and a given time by transferring the existing precipitation field along Lagrangian trajectories. Frequently, these methods assume that precipitation does not change over the time along the trajectories e.g., [91,[98][99][100][101][102][103][104]. This assumption is acceptable in case of stratiform precipitation for forecasts with lead times of several hours; however, in case of convective precipitation, the precipitation can change (even significantly) along the trajectories.…”
Section: Quantitative Precipitation Forecastmentioning
confidence: 99%
“…Defining the initial state of the atmosphere is critical to the skill of weather forecasts for time scales anywhere between nowcasting to the medium‐range (up to 10 days; Rabier, , Sokol & Zacharov, ). To initialize global numerical weather prediction (NWP) models, such as the Integrated Forecast System at the European Centre for Medium‐range Weather forecasting (ECMWF), data assimilation techniques are employed to produce an analysis using a vast quantity of observations from a diverse range of instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced continuous rank probability score (RCRPS; Eq. 7; Trinh et al, 2013) is computed as the CRPS (Brown, 1974;Matheson and Winkler, 1976;Unger, 1985;Stanki et al, 1989;Hersbach, 2000), reduced with the standard deviation of the observed discharge over the analysed time period (hereafter σ 2 ):…”
Section: Methodology Of Analysismentioning
confidence: 99%